Opioid-Free Anesthesia Technique for Anterior Cervical Discectomy and Fusion (ACDF): Anesthesia Management - Cobis, Albinus Yunus; Bisri, Dewi Yulianti; Rachman, Iwan Abdul (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Anterior cervical discectomy and fusion (ACDF) is a safe and effective surgical procedure to treat cervical spine pathology. ACDF treats Cervical Spondylotic Myelopathy (CSM), where degeneration of the cervical vertebrae compresses the spinal cord, causing sensory, motor, reflex, and bowel function impairment. The use of opioids can have unpleasant effects, hence opioid-free anaesthesia techniques were developed as a strategy to reduce this risk. A man, 62 years old, complained of weakness in the upper limbs until it was difficult to move the hands. Supportive examination revealed cervical myeloradiculopathy due to multiple hernia nucleus pulposus (HNP). Management of opioid-free anaesthesia techniques using multimodal analgesics. During the operation, haemodynamics were relatively stable. Extubation was performed in the operating room and then the patient was transferred to the intensive care unit. The choice of opioid-free anaesthesia technique in the case was to provide multimodal using specific agents that have anaesthetic or analgesic properties. Opioid-free anaesthesia methods that support the Enhanced Recovery after Surgery (ERAS) concept are considered highly beneficial in accelerating recovery time, reducing length and cost of treatment and minimizing opioid-related unpleasant risks. The opioid-free anaesthetic technique in this case report demonstrates the feasibility and benefits of opioid-free anaesthesia in effective pain management and minimizing opioid-related risks, especially in ACDF surgical procedures. This technique is in line with the ERAS protocol.